Welding Current Variation Determines Tensile Strength in MIG Joints: Variasi Arus Las Menentukan Kekuatan Tarik pada Sambungan MIG - Wijaya, Achmad Surya; Mulyadi (Indonesian Journal of Innovation Studies, 2025)
General Background: Welding is a critical process in manufacturing that determines the strength and reliability of material joints. Specific Background: Metal Inert Gas (MIG) welding is widely used due to its efficiency, but variations in welding current can significantly affect the mechanical properties of the welded material. Knowledge Gap: The optimal current variation for achieving maximum tensile strength in MIG welding is not always clearly defined for specific materials such as ST 37. Aims: This study aims to analyze the effect of welding current variation on the tensile strength of ST 37 material using the MIG welding method. Results: The findings indicate that different current levels produce varying tensile strengths, with one current variation resulting in the highest tensile strength compared to others. Novelty: The study provides experimental evidence of the relationship between welding current variation and tensile strength in ST 37 material using controlled parameter conditions. Implications: The results can be used as a reference for selecting appropriate welding parameters to achieve stronger and more reliable welded joints in industrial applications. Keywords: Welding, MIG Process, Tensile Strength, Current Variation, ST37 Steel Key Findings Highlights Highest strength observed at specific electrical input setting Mechanical performance varies across tested parameter levels Experimental comparison confirms parameter sensitivity in joining process